Answer:
To find the value of y when x is -4 in a scenario where y varies inversely with x, we can use the inverse variation equation:
y = k/x
where k is the constant of variation. To solve for k, we can substitute the given values of y and x into the equation:
6 = k/(-2)
To isolate k, we can cross-multiply:
6 * (-2) = k
-12 = k
Now that we have the value of k, we can use it to find the value of y when x is -4:
y = k/x
y = -12 / (-4)
y = 3
Therefore, when x is -4, y is equal to 3 in this inverse variation scenario.
Explanation: